Multiple hippocampal transection for mesial temporal lobe epilepsy: A systematic review. (October 2022) - Abramov, Irakliy; Jubran, Jubran H.; Houlihan, Lena Mary; Park, Marian T.; Howshar, Jacob T.; Farhadi, Dara S.; Loymak, Thanapong; Cole, Tyler S.; Pitskhelauri, David; Preul, Mark C.
Highlights: First patient-level systematic review of MHT for mesial temporal lobe epilepsy. Post-MHT seizure control analyzed for different surgical approaches and techniques. Postoperative memory outcome was grouped into verbal and nonverbal memory retention. Abstract: Purpose: Multiple hippocampal transection (MHT) is a surgical technique that offers adequate seizure control with minimal perioperative morbidity. However, there is little evidence available to guide neurosurgeons in selecting this technique for use in appropriate patients. This systematic review analyzes patient-level data associated with MHT for intractable epilepsy, focusing on postoperative seizure control and memory outcomes. Methods: The systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant articles were identified from 3 databases (PubMed, Medline, Embase) up to August 1, 2021. Inclusion criteria were that the majority of patients had received a diagnosis of intractable epilepsy, the article was written in English, MHT was the primary procedure, and patient-level metadata were included. Results: Fifty-nine unique patients who underwent MHT were identified across 11 studies. Ten (17%) of 59 patients underwent MHT alone. Forty-three (75%) of 57 patients who had a follow-up 12 months or longer were seizure free at last follow-up. With respect to postoperative verbal memory retention, 9 of 38 (24%) patient test scores did not change, 14 (37%) decreased, and 16 (42%) increased. With respect to postoperative nonverbal memory retention, 12 of 38 (34%) patient test scores did not change, 13 (34%) decreased, and 13 (33%) increased. Conclusion: There are few reported patients analyzed after MHT. Although the neurocognitive benefits of MHT are unproven, this relatively novel technique has shown promise in the management of seizures in patients with intractable epilepsy. However, structured trials assessing MHT in isolation are warranted.